THE EFFECT OF PERCEIVED EASE OF USE AND PERCEIVED USEFULNESS ON CUSTOMER SATISFACTION AND INTENTION TO CONTINUE USE E-WALLET IN THE COMMUNITY OF LHOKSEUMAWE CITY - Sapna Biby; Fachry Zaldi; Mariyudi; Naufal Bachri; Adnan; Ikramuddin (CV. Radja Publika, 2025)
This study examines the influence of Perceived Ease of Use and Perceived Usefulness on Customer Satisfaction and Intention to Continue Using E-Wallets in Lhokseumawe City. The sample in this study was 140 people from Lhokseumawe City who had used e-wallets. Data collected through questionnaires were analyzed using data analysis methods using Structural Equation Modeling (SEM) which was operationalized with the Analysis of Moment Structure (AMOS) tool. The results of the study indicate that PEU and PU have a significant effect on CS and IU. And CS has a direct effect on IU. Then, in testing the indirect effect, CS was found to play a role as a partial mediating variable in the relationship between PEU and PU on IU. The results of this study are expected to be important information for e-wallet brand providers in making policies related to product development. The results of this study also provide important information for consumers or e-wallet users in deciding to use e-wallets to support transactions through digital marketing.